Reviewing Assessment Tools for Measuring Country Statistical Capacity - Hai-Anh H. Dang; John Pullinger; Umar Serajuddin; Brian Stacy (Global Labor Organization (GLO), 2024)
Country statistical capacity is increasingly recognized as crucial for development, but no academic study exists that reviews the available assessment tools. We offer the first review study that fills this gap, paying particular attention to data and practical measurement challenges. We compare the World Bank's recently developed Statistical Performance Indicators and Index (SPI) with other widely used indexes such as the Open Data Inventory index (ODIN), the Global Data Barometer index (GDB), and other regional and self-assessment tools. We find that the indexes bring their own advantages regarding their data sources, number of indicators, measurement focus, coverage of country and time periods, and correlation with common development indexes. Specifically, the ODIN covers most countries, the GDB collects data through its surveys, and the SPI offers clearer mathematical foundations and somewhat stronger correlation with Sustainable Development Goals indicators. We offer further thoughts on the potential mechanisms through which these tools can bring positive impacts on economic activities and some political economy concerns, as well as future directions of development.
Keywords: C8; H00; I00; O1; 330; statistical capacity; statistical performance; statistical indicators; statistical capacity index; national statistical system